Carbon dots: promising biomaterials for bone-specific imaging and drug delivery. Issue 44 (7th November 2017) - Peng, Zhili; Miyanji, Esmail H.; Zhou, Yiqun; Pardo, Joel; Hettiarachchi, Sajini D.; Li, Shanghao; Blackwelder, Patricia L.; Skromne, Isaac; Leblanc, Roger M.
Abstract : Bone-related diseases and dysfunctions are heavy burdens on our increasingly aged society. In this study, carbon dots have been introduced as highly promising biomaterials for bone-related bioimaging and drug delivery due to their high affinity and specificity bone-binding properties. Abstract : Bone-related diseases and dysfunctions are heavy burdens on our increasingly aged society. One important strategy to relieve this problem is through early detection and treatment of bone-related diseases. Towards this goal, there has been constant interest in developing novel bone-specific materials for imaging and drug delivery. Currently, however, materials that have high affinity and specificity towards bone are very limited. Carbon dots (C-dots) synthesized from carbon nanopowder bind to calcified bones in vivo with high affinity and specificity. In this study we show that bone binding is highly unique to a specific type of C-dot, and that this binding is non-toxic. Significantly, C-dots derived from other raw materials did not show any bone binding properties. These differences are attributed to the differences in surface chemistry of C-dot preparations, highlighting the heterogeneous nature of C-dots. Importantly, bone-binding by carbon nanopowder derived C-dots is not significantly altered by chemical functionalization of their surface. These unique properties indicate the potential applications of carbon nanopowder-derived C-dots as highly bone-specific bioimaging agents and drug carriers.